P3.051 Pre-Vaccination Prevalence of Infections with 25 Low-Risk Human Papillomavirus (HPV) Types Among 1000 Slovenian Women Screened For Cervical Cancer in 2010. (13th July 2013) - Učakar, V; Poljak, M; Oštrbenk, A; Klavs, I
Abstract : Background: Our objective was to estimate pre-vaccination prevalence of cervical infections with 25 non-high-risk human papillomavirus (HPV) types, referred to as low-risk HPV (LR-HPV) types, regardless of and without the coexistence of high-risk HPV (HR-HPV) types among Slovenian women 20–64 years old screened for cervical cancer. Methods: 1000 cervical specimens randomly selected from 4455 specimens collected in the Slovenian HPV prevalence survey with a nationally wide coverage in 2010 were tested with Linear Array HPV Genotyping Test. Results: Prevalence of cervical infections with any of the 25 LR-HPV types was 10.0% (95% CI: 8.1%–11.9%) and with exclusively LR-HPV types 4.5% (95% CI: 3.2%–5.8%). Prevalence of infections with any LR-HPV types among women with normal cytology was 8.8%, with atypical squamous cells of undetermined significance (ASC-US) 30.4%, with low grade squamous intraepithelial lesions (LSIL) 60.0%, and with high grade squamous intraepithelial lesions (HSIL) 7.7%. LR-HPV types without coexisting HR-HPV types were found in 4.0% of women with normal cytology, 26.1% with ASC-US, 6.7% with LSIL, and none with HSIL. Infections with exclusively HPV 6 or HPV 11 were not found. Conclusions: LR-HPV type cervical infections without coexisting HR-HPV infections were common among Slovenian women screened for cervical cancer with ASC-US, while rare in those with pathological cytology result. With respect to organised cervical cancer screening programme in Slovenia our results suggest that HR-HPV testing based triage that complements the follow-up cytology in the Slovenian cancer screening programme since 2010, will contribute to some reduction in the Slovenian NCCSP follow-up burden, especially among women with ASC-US and some decrease in related patient anxiety.